2014
DOI: 10.4081/jlimnol.2014.1082
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of allochthonous and autochthonous energy inputs in an alpine stream

Abstract: Despite the enormous importance of alpine streams, information about many aspects of their ecology is still insufficient. Alpine lotic systems differ in many environmental

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Similarly, the temperature is too low and water force too erosive to allow for the growth of primary producers, limiting grazers as well. For instance, Fenoglio et al (2014) observed that streams located above the tree line have a reduced input of allochthonous organic matter in autumn, because the organic matter input becomes trapped under ice and snow cover during the entire cold season, reaching streams during late spring, when meltwater collects and transports particles throughout the catchment. In this case, the food web depends on in-stream primary production, and benthic communities are characterized by a greater proportion of scrapers and species with higher trophic plasticity than those of downstream sections (Körner 1998;Fenoglio et al 2014).…”
Section: The Role Of Natural Discontinuitiesmentioning
confidence: 99%
“…Similarly, the temperature is too low and water force too erosive to allow for the growth of primary producers, limiting grazers as well. For instance, Fenoglio et al (2014) observed that streams located above the tree line have a reduced input of allochthonous organic matter in autumn, because the organic matter input becomes trapped under ice and snow cover during the entire cold season, reaching streams during late spring, when meltwater collects and transports particles throughout the catchment. In this case, the food web depends on in-stream primary production, and benthic communities are characterized by a greater proportion of scrapers and species with higher trophic plasticity than those of downstream sections (Körner 1998;Fenoglio et al 2014).…”
Section: The Role Of Natural Discontinuitiesmentioning
confidence: 99%
“…The terrestrial-aquatic linkages are well known, the most plausible cause for this being the research on allochthonous resource use (mainly terrestrial leaves and terrestrial invertebrates) by organisms inhabiting stream food webs (Nakano et al, 1999a;Nakano and Murakami, 2001;Alvim et al, 2015;Fenoglio et al, 2015). In fact, inputs of terrestrial invertebrates from riparian canopy cover may represent an important food resource for stream-dwelling fish species (Kawaguchi and Nakano, 2001;Utz and Hartman, 2007;Syrjänen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Apennine rivers (Bottazzi et al, 2011;Fenoglio, Bo, Cammarata, López-Rodríguez, & de Figueroa, 2014). These works suggest that the major forces shaping invertebrate communities seemed to be related to the Alpine climate and especially to snow accumulation and melting with the consequent substantial discharge variations.…”
Section: Seasonal Distribution Of Invertebrates Was Also Identified Inmentioning
confidence: 97%